Considerations for the translation of nutrient recommendations as dietary plans for infants, children, and adolescents as reported in Italian Guidelines for healthy eating - Rossi, Laura; Martone, Deborah; Piccinelli, Raffaela; Buonocore, Pasquale; Ghiselli, Andrea; , the Working Group on Pediatric Nutrition of Italian Dietary Guidelines; Caroli, Margherita; Giovannini, Marcello; Morino, Giuseppe; Scaglioni, Silvia; Vania, Andrea; Verduci, Elvira (Frontiers in Nutrition, 2022)
Healthy eating in childhood and adolescence is important for proper growth and development and to establish a foundation for future dietary habits. This paper aims to describe the process of elaboration of dietary plans for pediatric ages highlighting the critical points related to the application of the Italian nutrient recommendations. National databases on food composition data were used to compile the dietary plans. Starting from the definition of serving size for adults, the suggested portion size for pediatric ages was shaped to produce dietary plans adequate to the different classes of age. Items from “cereals and derivatives”, “milk”, “fruit”, “vegetables”, “olive oil”, and “water” groups were included daily. Pizza was included once a week. Sweets and snacks were gradually introduced, once a week in infants up to 5 times a week in adolescents. Legumes were provided 3 times a week, as a source of vegetable and sustainable proteins. The main critical aspect of the dietary plans was related to the monotony, especially for snacks and breakfasts. This work demonstrated the limits of the translation of Italian nutrient recommendations into dietary plans for the pediatric age. Keeping the protein intake in the range of 8-12% of daily energy resulted in inadequate provision of calcium and iron. Others critical points were the reference values for body weight and for physical activity. The proposed dietary plans are adequate with regards to food composition, the intake of energy and several nutrients, and in terms of food selection. However, their implementations require actions, information, and advocacy.